Auditor Reputation and Earnings Management: International Evidence from the Banking Industry - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2010)
We examine the relation between auditor reputation and earnings management in banks using a sample of banks from 29 countries. In particular, we examine the implications of two aspects of auditor reputation, auditor type and auditor industry specialization, for earnings management in banks. We find that both auditor type and auditor industry specialization moderate benchmark-beating behavior in banks. However, we find that once auditor type and auditor industry specialization are included in the same tests, only auditor industry specialization has a significant impact on constraining benchmark-beating behavior. In tests related to income-increasing abnormal loan loss provisions, we find in separate tests that both auditor type and auditor expertise constrain income-increasing earnings management. Again, in joint tests, only auditor industry expertise has a significant impact on constraining income-increasing earnings ma